Estrés Académico Y Bruxismo En Estudiantes De Odontología De La Universidad Antonio Nariño Sede Ibagué 2019 - López Ortiz, Diana Katerin; Manios Andrade, Mario Alejandro (Universidad Antonio Nariño, 2021)
It was determined that 100% of the students have the knowledge about what bruxism is. Regarding stressful situations, 46% of students indicated that they have never felt pressure in the face of competition with colleagues for grades. 44% students indicated that sometimes they feel stress because they do not understand the topics and the limited time to do work. In the physical reactions 40% students indicated that some present drowsiness or greater need for sleep. Psychological reactions 36% of the students indicated that they rarely present concentration problems in the clinics. Behavioral reactions 46% of the students stated that they never present conflicts or have a tendency to argue. The strategy that students use the most according to this study is the search for information on the subject of the class with 38.4%.